The canonical RPA complex interacts with Est3 to regulate yeast telomerase activity - Corinne A. Moeller-McCoy; Thomas A. Wieser; Johnathan W. Lubin; Abigail E. Gillespie; Jocelyn A. Ramirez; Margherita Paschini; Deborah S. Wuttke; Victoria Lundblad (Proceedings of the National Academy of Sciences, 2025)
In most eukaryotic organisms, cells that rely on continuous cell division employ the enzyme telomerase which replenishes chromosome termini through the addition of telomeric repeats. In budding yeast, the telomerase holoenzyme is composed of a catalytic core associated with two regulatory subunits, Est1 and Est3. The Est1 protein binds a telomere-specific RPA-like complex to recruit telomerase to chromosome ends. However, the regulatory function of the Est3 subunit has remained elusive. We report here that an interaction between Est3 and the canonical RPA complex is required for in vivo telomerase function, as revealed by mutations in RPA2 that confer an Est (Ever shorter telomeres) phenotype, characteristic of a defect in the telomerase pathway. Binding between RPA and telomerase, which is supported by compensatory charge-swap mutations in EST3 and RPA2 , utilizes a surface on Est3 that is structurally analogous to an interface on the human TPP1 protein that is required for telomerase processivity. Mutations in a subset of conserved DNA contact residues in RPA also result in short telomeres and senescence, which we show is due to a requirement for DNA binding after RPA interacts with telomerase. We propose that once RPA forms a complex with telomerase, RPA utilizes a subset of DNA-binding domains to stabilize the interaction between the telomerase active site and telomeric substrates, thereby facilitating enzyme processivity. These results, combined with prior observations, show that yeast telomerase interacts with two different high-affinity ssDNA-binding complexes, indicating that management of single-stranded DNA is integral to effective telomerase function.